Stock Market Response to Economic Growth and Interest Rate Volatility: Evidence from Nigeria - Ayopo, Babajide Abiola; Isola, Lawal Adedoyin; Olukayode, Somoye Russel (International Journal of Economics and Financial Issues, 2016)
This study examined the relationship between macroeconomic variable volatility and stock market return within the context of Blanchard (1981) extension of the Hicks (1937) IS-LM hypothesis, using EGARCH estimation techniques to analysis monthly data sourced on the Nigerian economy from January 1985 to December 2013. Our result shows that stock prices responds significantly to innovations in the interest rate and the RGDP, we therefore recommends that policy makers on the one hand should consider volatility in both the interest rate and the RGDP when making policies aimed at enhancing stock market development. On the other hand, market practitioners are expected to make provisions for volatility in interest rate and the RGDP when making portfolio decisions. Keywords: Interest rate, Real Gross Domestic Product, All Share Price, Volatility, EGARCH JEL Classifications: C22, G01, G14, G15